A portable biosensor system for pathogen diagnostic applications - Yang, Lang, author; Filer, Jessie, author; Chen, Tom, author (Colorado State University. Libraries, 2017)
The platform uses the electrochemical impedance spectroscopy (EIS) technique for pathogen detections. It includes sensor front end, stimulus generation, analog sensor data acquisition and conditioning, digital-to-analog conversion, back-end digital signal processing, wireless interface and a user phone app. The platform is powered by a USB based rechargeable battery at 3.3V. At a area cost of 28cm2. An average error of 2.6% is achieved compared to commercial counterpart.
321 - Lang Yang
A handheld electrochemical sensing platform for point-of-care diagnostic applications
Keywords: biosensor; EIS; point-of-care; pathogen detection